2009
DOI: 10.1097/pcc.0b013e3181c0141b
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes among neonates, infants, and children after extracorporeal cardiopulmonary resuscitation for refractory in-hospital pediatric cardiac arrest: A report from the National Registry of CardioPulmonary Resuscitation*

Abstract: Forty-four percent of pediatric patients who failed conventional cardiopulmonary resuscitation from in-hospital cardiopulmonary arrest and who were reported to the National Registry of CardioPulmonary Resuscitation database as treated with extracorporeal cardiopulmonary resuscitation survived to hospital discharge. The majority of survivors with recorded neurologic outcomes were favorable. Patients with cardiac illness category were more likely to survive to hospital discharge after treatment with extracorpore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
7
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(154 citation statements)
references
References 43 publications
5
135
7
7
Order By: Relevance
“…25 Observational data support the use of ECPR for infants and children in cardiac arrest (especially those with underlying cardiac disease) in the in-hospital critical care setting, when patients are refractory to conventional resuscitation, and when the necessary ECPR protocols, expertise, and equipment exist. 26,27 No evidence exists to support its routine use for cardiac arrest in the out-of-hospital setting.…”
Section: Intra-arrestmentioning
confidence: 99%
“…25 Observational data support the use of ECPR for infants and children in cardiac arrest (especially those with underlying cardiac disease) in the in-hospital critical care setting, when patients are refractory to conventional resuscitation, and when the necessary ECPR protocols, expertise, and equipment exist. 26,27 No evidence exists to support its routine use for cardiac arrest in the out-of-hospital setting.…”
Section: Intra-arrestmentioning
confidence: 99%
“…From the Extracorporeal Life Support Registry, Thiagarian et al [183] found that overall survival to hospital discharge after ECPR was 38%. Raymond et al [184] analyzed the National Registry of Cardiopulmonary Resuscitation and found survival to discharge of 44%, remarkably, with 95% reported having favorable neurological outcome. Neurological complications from ECPR, including hemorrhage, infarction, and brain death are common.…”
Section: Advances In Cerebral Resuscitation In Childrenmentioning
confidence: 99%
“…However, survival statistics for ECPR are more encouraging, with a general rate of success of near 40% to 60%. [2][3][4][5][7][8][9][10][11][12][13][19][20][21][22][23][24][25][26] Multi-institutional data obtained in 2012 from the Extracorporeal Life Support Organization (ELSO), an international registry and database of ECMO treatment, demonstrated that ECPR was successful for 934 out of 2236 neonatal and pediatric patients, with survival to discharge of 39% for neonates and 40% for children. Other retrospective, single-institution studies have shown survival rates as high as 72% to 80%.…”
Section: The Benefits Of Ecprmentioning
confidence: 99%